Urgensi Maqashid Syariah Dalam Pengembangan Ekonomi - Satria Darma (STIS Ummul Ayman, Meureudu, Pidie Jaya, Aceh, Indonesia, 2021)
This study aims to analyze the urgency of Islamic maqashid in economic development. This research uses exploratory study method, descriptive analysis in analyzing secondary data related to these problems. The results show that maqashid on the Theory of Economic Behavior can be seen in: Economic Problems, Wants versus Needs, and Mashlahah versus Utility.